INFLUENCE OF PROJECT PLANNING STRATEGY ON IMPLEMENTATION OF ENERGY ACCESS PROJECTS IN UNDERSERVED COUNTIES IN KENYA - Avedi, Evans Kituzi; Mulwa, Dr. Angeline Sabina; Kyalo, Prof. Dorothy Ndunge (Advances in Social Sciences Research Journal, 2020)
The purpose of this article was to examine the extent to which project planning influence implementation of rural energy access projects in underserved counties in Kenya. The unit of analysis was households, commercial centers, schools, hospitals and a sample size of 373 respondents was selected from a target population of 5,604 respondents in areas where rural electrification has been implemented in underserved counties in Kenya through stratified sampling and purposive sampling techniques. Data was collected from the respondents through questionnaires, interviews and observation. The research outcome depicted that project planning had significant influence on the implementation of energy access projects in underserved counties in Kenya. The coefficient of determination R2 was 0.042 and it depicted that project planning explained 4.2 % of variations in implementation of energy access projects in underserved counties in Kenya. The remaining 95.8% of variations in implementation of energy access projects in underserved counties remained unexplained and were explained by other variables other than project planning that were not captured in this model. The overall F statistic of F = 4.399(p = 0.05) was statistically significant at P=0.000<0.05 hence was suitable to measure project planning. This study found out that while each country has its own priorities and needs, many have invested in policy reforms and capacity building, mainstreamed energy access within development programs, and used various incentive-based instruments to catalyze finance for energy access markets.